Hyperfine splitting of [Al VI] 3.66 mu m and the Al isotopic ratio in NGC 6302 - Casassus, S; Storey, P; Barlow, M; Roche, P (2005)
The core of planetary nebula NGC 6302 is filled with high-excitation photoionized gas at low expansion velocities. It represents a unique astrophysical situation in which to search for hyperfine structure (HFS) in coronal emission lines from highly ionized species. HFS is otherwise blended by thermal or velocity broadening. Spectra containing [Al VI] 3.66 μm 3P 2 ← 3P 1, obtained with Phoenix on Gemini South at resolving powers of up to 75000, resolve the line into five hyperfine components separated by 20-60 km s -1 as a result of the coupling of the I = 5/2 nuclear spin of 27Al with the total electronic angular momentum J. The isotope 26Al has a different nuclear spin of I = 5, and a different HFS, which allows us to place a 3σ upper limit on the 26Al/ 27 AI abundance ratio of 1/33. We measure the HFS magnetic dipole coupling constants for [Al VI], and provide the first estimates of the electric quadrupole HFS coupling constants obtained through astronomical observations of an atomic transition. © 2005 RAS.